Accelerating And Sustaining Growth. - Virmani, Arvind (IMF Working Papers., 2012)
The paper reviews and draws lessons from the experience of fast growing economies including a sub-set of these termed High Growth Economies (HGEs) with a decadal rate of over 7 per cent. It then reviews the history of the Indian growth acceleration following the reforms of the 1990s and its future prospects given the recent slowdown. It analysis the potential dangers and reasons for India's growth slowdown and proposes policy reforms for sustaining fast growth.